Digital payments, the cashless economy, and financial inclusion in the United Arab Emirates: Why is everyone still transacting in cash? - Jeremy Srouji (Journal of Risk and Financial Management, 2020)
Since the oil price downturn of 2015, the United Arab Emirates and fellow Gulf Cooperation Council countries have worked hard to expand digital payments in the interest of improved tax and revenue collection, transparency, and security. Yet despite a deep transformation and diversification of their payment eco-systems and the formalization of plans to become "cashless economies" modelled on South Korea and Sweden, cash continues to dominate payments in both countries. While industry players typically attribute the prevalence of cash in the region to questions of infrastructure readiness, transaction costs, and cyber-security, this paper finds that plans to expand digital payments at the expense of cash may not be well-adapted to countries with high levels of socio-economic inequality. It proposes a link between socio-economic inequality and use of cash in emerging economies, and concludes that it may be better to not view the relationship between cash and digital payments in binary zero-sum terms, until there is a better understanding of the socio-economic, technological, and policy context in which countries like South Korea and Sweden have managed to reduce their reliance on cash in favor of a diversified digital payments eco-system.
Keywords: 330; financial inclusion; complementary currencies; cashless economy; digital payments; Gulf Cooperation Council; inequality; non-cash transactions; oil economies; remittances